MENINGKATKAN AKTIVITAS SISWA, MOTIVASI, KARAKTER WASAKA, DAN HASIL BELAJAR MENGGUNAKAN MODEL PROJECT BASED LEARNING (PjBL) DAN SNOWBALL THROWING TERINTEGRASI STEM PADA MUATAN IPA KELAS VA SDN SN SUNGAI MIAI 5 BANJARMASIN - Ardana, Muhammad Ridha; Annisa, Muhsinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study identifies issues such as low student activity, motivation, WASAKA character (religious and responsibility), and learning outcomes in Science Education. These problems stem from teacher-centered methods, lessons lacking engagement and relevance, low self-confidence, and student dissatisfaction. Students show a lack of seriousness in prayer, religious values are insufficiently integrated into lessons, and students do not complete assignments or actively participate. The solution proposed is using the Project-Based Learning (PjBL) model and Snowball Throwing integrated with STEM. The study uses Classroom Action Research (CAR) with two cycles involving 34 students of class 5A at SDN SN Sungai Miai 5 in 2023/2024. Results show that PjBL and Snowball Throwing integrated with STEM significantly improve student activity, motivation, WASAKA character, and learning outcomes. In Cycle I, student activity was 47.06%, motivation was 55.88%, WASAKA character was 47.06%, cognitive outcomes were 58.82%, and psychomotor outcomes were 52.94%. In Cycle II, these percentages increased to student activity 88.24%, motivation 94.12%, WASAKA character 91.18%, cognitive learning outcomes 91.18%, and psychomotor learning outcomes 94.12%.